Renal limited ANCA-positive vasculitis: a rare manifestation of a rare disease - Ali Jawad Jang Khan MD; Noman Ahmed Jang Khan MD (SAGE Publishing, 2020)
Pauci-immune crescentic glomerulonephritis is the most common variant of rapidly progressive glomerulonephritis, accounting for approximately 80% of total cases. Most of the cases are associated with the presence of anti-neutrophil cytoplasmic antibody (ANCA) and are usually referred to as ANCA-associated vasculitis. A 68-year-old male with no previous renal history presented with complaints of shortness of breath, cough, and bilateral leg swelling for 2 weeks. Initial workup was significant for creatinine elevated at 2.9 mg/dL, blood urea nitrogen at 65 mg/dL, and glomerular filtration rate of 27 mL/min. Further workup was unremarkable for any significant abnormality. Subsequently patient's kidney function worsened, and temporary hemodialysis was started. Kidney biopsy was performed, which later came back significant for necrotizing arteritis, multifocal, with focal necrotizing and crescentic glomerulonephritis, pauci-immune type. High-dose corticosteroids were administered, and good clinical response was noticed. This is a very rare case of renal limited pauci-immune crescentic glomerulonephritis with annual incidence of 7 to 10 cases per million every year in the United States. The absence of involvement of other organs makes our case even rarer. Mortality is as high as 90% in untreated patients and aggressive therapy with glucocorticoids and cyclophosphamide or rituximab are the mainstay of treatment. The presence of significant renal impairment in the absence of other organs involvement in our patient makes it a very unique presentation of ANCA-positive vasculitis.